Broken Promises? NAFTA, Immigration, and ‘Shadow’ Regionalism - Fanny Lauby (IdeAs)
The reduction of immigration was never an official objective of the North American Free Trade Agreement. Yet, it was generally supposed to be one of its long-term consequences. Fifteen years later, Mexican immigration to the United States has in fact increased. The agreement has failed to reduce the attractiveness of the U.S. labor market for Mexican workers and to provide sustainable alternatives to immigration. Over the same period of time, American politicians and the American media have consistently embraced a narrative in which immigration control has become a matter of national security. A paradox has emerged from these two conflicting trends. While the measures taken by the federal government have failed to prevent unauthorized migrants from entering the country, they have also encouraged them to stay longer in the U.S. by making border-crossings too risky. The 1990s therefore witnessed a significant growth of the undocumented population of the United States. This paper analyzes the emergence of a “shadow” regional system between Mexico and the U.S., driven by immigrants themselves, as well as those who profit from undocumented immigration, rather than by institutional actors. This shadow integration is the product of two types of flows: people moving north of the border and, increasingly, remittances moving south. Remittances in turn reinforce immigration trends since they perpetuate the expectations of immigrants. This article examines the development of this parallel form of integration that has taken place at the same time as the implementation of the trade agreement, beyond the control of the Mexican and American governments.